The moral imagination : The art and soul of building peace - Lederach, John Paul (New York Oxford, 2005)
This new book represents his thinking and learning over the past several years. He explores the evolution of his understanding of peacebuilding by reflecting on his own experiences in the field. Peacebuilding, in his view, is both a learned skill and an art.
Includes bibliographies and index (p.187-200)
Keywords: Tham khảo